Ultrafast plasma method allows rapid immobilization of monatomic copper on carboxyl-deficient g-C3N4 for efficient photocatalytic hydrogen production - Xu, Shuchang; Zhang, Zhihao; Wang, Daqian; Lu, Junyang; Guo, Ying; Kang, Shifei; Chang, Xijiang (Frontiers in Chemistry, 2022)
Transition-metal monometallic photocatalysts have received extensive attention owing to the maximization of atomic utilization efficiency. However, in previous related works, the single atom loading and the stability are generally low due to the limited anchor sites and mechanisms. Recently, adding monatomic transition-metal to defective carbon nitrides has a good prospect, but there is still a lack of diversity of defect structures and preparation techniques. Here, a strategy for preparing defect-type carbon-nitride-coupled monatomic copper catalysts by an ultrafast plasma method is reported. In this method, oxalic acid and commercial copper salt are used as a carboxyl defect additive and a copper source, respectively. Carbon nitride samples containing carboxyl defects and monatomic copper can be processed within ten minutes by one-step argon plasma treatment. Infrared spectroscopy and nuclear magnetic resonance prove the existence of carboxyl defects. Spherical aberration electron microscopy and synchrotron radiation analysis confirm the existence of monatomic copper. The proportion of monatomic copper is relatively high, and the purity is high and very uniform. The Cu PCN as-prepared shows not only high photo-Fenton pollutant degradation ability but also high photocatalytic hydrogen evolution ability under visible light. In the photocatalytic reaction, the reversible change of Cu+/Cu2+ greatly promotes the separation and transmission of photogenerated carriers and improves the utilization of photoelectrons. The photocatalytic hydrogen evolution rate of the optimized sample is 8.34 mmol·g-1·h-1, which is 4.54 times that of the raw g-C3N4 photocatalyst. Cyclic photo-Fenton experiment confirms the catalyst has excellent repeatability in strong oxidation environment. The synergistic mechanism of the photocatalyst obtained by this plasma is the coordination of single-atom copper sites and carboxyl defect sites. The single copper atoms incorporated can act as an electron-rich active center, enhancing the h+ adsorption and reduction capacity of Cu PCN. At the same time, the carboxyl defect sites can form hydrogen bonds to stabilize the production of hydrogen atoms, and subsequently convert to hydrogen because of the unstable hydrogen bond structure. This plasma strategy is green, convenient, environment-friendly and waste-free. More importantly, it has the potential for scale-up production, which brings a new way for the general preparation of high-quality single-atom catalysts.